Multiple records and polymorphism of Parastichopus regalis (Cuvier, 1817) (Echinodermata: Holothuroidea: Stichopodidae) along the Algerian coast - Khodja, Ihcene; Mezali, Karim; Thandar, Ahmed S. (Zootaxa, 2021)
The family Stichopodidae is represented in the Mediterranean Sea by the genus Parastichopus which includes two non-endemic species; Parastichopus tremulus (Gunnerus, 1767) and Parastichopus regalis (Cuvier, 1817). On the Algerian coast (southwestern Mediterranean Sea), two morphotypes of P. regalis were observed, one with dark spots on the dorsal surface and the other non-spotted. In total, 65 individuals of P. regalis were recorded from 22 stations along the Algerian coast during an oceanographic campaign. Twelve individuals (6 of each morphotype) were used for a comparative study of the morphological (including endoskeletal) characteristics. Table ossicles, the only ossicles of the body wall of the two morphotypes of P. regalis, are here compared with regard to the disk diameter of the tables and the total area of the surface of the disc. Statistical analysis did not show any significant differences between the spotted and the non-spotted morphotypes.